THE ANALYSIS OF CONSTRUCT VALIDITY OF WORK READINESS SCALE USING RASCH MODEL - Gita Ayu Rachmawati; Eka Sakti Yudha (Universitas Pendidikan Indonesia, 2022)
This article presents research on the analysis of construct validity of work readiness scale using rasch model. The results of the analysis show that the theoretical construct measures one variable of work readiness. Work readiness is important for final year students. A quantitative approach is used as a research method with a survey design. The participants in this study were 245 undergraduate students at the Indonesian Education University batch 2018. The research instrument refers to aspects developed by Robert P. Brady which were analyzed using the Rasch Model. The results showed that the Cronbach Alpha value of 0.71 means that the reliability between the person and item is good, while the item reliability is 0.99 which means the instrument item is very good. This scale meets the criteria because it already has good psychometric properties so that it can be used to determine the level of work readiness.